Medijska reprezentacija žensk v politiki - Fabjančič, Nina (Teorija in praksa, 1999)
Taking a constructivist paradigm as the starting point, the author analyses media texts dealing with women in politics. The relation between femininity and politics is characterized by a tension which does not originate in conflicting 'essences' of both but I on a contrary, a result of historically discoursively formed dominant constructions of femininity and politics. In media texts female politicians are not treated primarily as persons in politics. Their representations are marked by the dominant discourse of femininity. In the article, the focus is put on the construction of women as belonging to the private sphere and the construction of women as public bodies. The author illustrates their manifestations using the examples of referential media texts regarding female politicians.
Keywords: woman; ženske; mass media; množični mediji; teksti; discourse; diskurz; spol; politics; politika; ženskost